Factores sociales que han motivado la participación de la población en el ejercicio de una ciudadanía inclusiva en el aa.hh. albujar y guarniz - guadalupe en el año 2013. - Arias Terán, Carolina Elizabeth (2013)
This thesis report shows on descriptive and qualitative way to the social factors that encourage the participation of the population in the exercise of citizenship inclusive, taking into account the different participatory processes should be open to all potentially interested citizens on the subject of public decisions. Experiences in the different areas of the territory have shown us that while most open are the participatory exercises to political and cultural diversity of our society, the greater their roots in national institutions and stronger will be its legitimacy against Governments. This implies that participation should reflect the social complexity of the different interests which have the right to be represented in the participatory spaces. In the AA.HH. Albujar and Guarniz - Guadalupe, which is our space where we have developed our research, the partner actors come to be: authorities of each Committee's progress and development investigated, each studied sector leaders, neighbors, authorities and non-governmental, and at the same time as all these interact, engage, and articulated in one way or another to obtain a better development in their localities, sectors, neighborhoods, villages trying to achieve improvements in different services that people seek to improve their quality of life. From our perspective the progress and development committees are very important, useful and very necessary, because they are closer to the population masses institutions and are the spokespersons of their needs and concerns against the administration of municipalities and Government agencies are also those who organize and motivate the citizens for the efforts of his works and projects. The same has been taken into account qualitative tools like semi-structured interview to identify and meet the different aspects related to the exercise of an inclusivecitizenship